Characterizing probiotic profiles using genomic and metabolomic insights into chicken cecum-derived Bacillus subtilis YB-114246 - Yang, Jiajun; Li, Ying; Wang, Jing; Zhang, Bo; Zhang, Hao (Frontiers in Microbiology, 2025)
IntroductionThe present study aimed to explore the genetic profile and annotate the metabolic profile of chicken cecum-derived B. subtilis YB-114246, which has been used in laying hens.MethodsThe complete genome of B. subtilis YB-114246 was analyzed and its probiotic metabolic profile was identified using genomic and metabolomic assays.Results and discussionB. subtilis YB-114246 possessed a chromosome containing 4,673,022 bp with a G+C content of 55.03%. The complete genetic sequence indicated that > 40% of the genes were coding sequences related to nutritional transportation and metabolism. B. subtilis YB-114246 harboring more unique genetic clusters played a role in the metabolism of macro molecular substances and synthesized more secondary metabolites. These genes are involved in glycan metabolism, amino acid and vitamin biosynthesis, and they also contribute to nutrient absorption and utilization in chickens. In this study, nonspecific virulence factor-related genes were identified in the genome of B. subtilis YB-114246. The metabolic profiles indicated that the primary functional substances were amino acids, phospholipids, eicosanoids, nucleotides, polyketides, and non-ribosomal peptides. The activities of digestive enzymes cellulase, amylase, protease, and lipase in fermented liquid of B. subtilis YB-114246 were 33.49, 1.23, 9.01, and 0.49 U/mL respectively. Correlation analysis between laying performance and metabolites showed that riboflavin, p-acetaminobenzoic acid, and 6-hydroxyhexanoic acid exhibited promoting effects. Riboflavin synthesized and secreted by B. subtilis YB-114246 reached 6.76 μg/L. The synthesis pathway predicted using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database originates from the purine metabolism and is involved in the pentose phosphate pathway in ribosomes. The utilization and recycling patterns of riboflavin were modeled, revealing a reciprocal relationship with the host.ConclusionOur findings revealed that the abundant nutritional genes and the production of functional metabolites by B. subtilis YB-114246 supplementation may enhance the laying performance of aged hens by improving digestive abilities.